Evaluasi Proses Penyusunan Laporan Keuangan Dan Pajak Di Kantor Jasa Akuntan Drs. Suwarno, Mm., Ak., Ca Jember - Rofidhatul Khoiriyah; Quri Arifatma Sari; Nabilatul Nur Laily; Mohammad Daud Rosyidi (Gudang Jurnal Multidisiplin Ilmu, 2024)
The preparation of financial and tax reports has a very important role in determining the success and compliance of an entity with applicable regulations and standards. The accounting services firm is the entity responsible for compiling these reports for its clients. Therefore, evaluation of the process of preparing financial and tax reports at accounting services firms becomes relevant to ensure the quality, accuracy and compliance of these reports. The aim of this research is to evaluate the effectiveness and efficiency of preparing financial and tax reports in accounting services offices. This includes analysis of existing processes, use of technology in preparing reports, and understanding taxes. In this way, it is hoped that areas where improvements are needed to improve service quality and compliance with applicable regulations can be identified. This data was collected through literature reviews and interviews with accounting practitioners and analysis of related documents. Apart from that, direct observation of the report preparation process was also carried out to gain a more in-depth understanding. The research results show that although many accounting firms have implemented best practices in preparing financial and tax reports, there are still several areas where improvements can be made. This includes increased use of technology to increase efficiency and increased collaboration between accounting teams and clients to ensure better compliance. By implementing the recommendations resulting from this research, it is hoped that accounting services firms can improve the services they provide and ensure better compliance with accounting and tax standards